XX ӘСИР ҲӘМ XXI ӘСИР БАСЛАРЫНДА ҚАРАҚАЛПАҚ ЭПОСЛАРЫНЫҢ СЫРТ ЕЛЛЕРДЕ ҮЙРЕНИЛИЎИ МӘСЕЛЕЛЕРИ - Алламбергенова, Г.К.; Бахадырова, С.Б. (FAN va JAMIYAT, 2016)
The article is devoted to the issues of study of the Karakalpak epos by foreign scholars in the XX-th and at the beginning of the XXI- st century. There have been analyzed their research works, devoted to the study and propaganda of Karakalpak eposes. Special attention is given to the evaluation of the works of the German scholar Carl Reikhel done at the end of the XX-th and at the beginning of the XXI-st century and devoted to the study and publication of the Karakalpak folklore epos «Edige».